Fundaments of Positive Logic - Poizat, B. (Ye.A.Buketov Karaganda State University Publishing house, 2013)
The main purpose of this paper is to give the basic concepts of positive logic. The content of this work is the essence of the course of lectures given by me in the Academican Ye.A.Buketov Karaganda State University in the months of April and May 2013.
Позитивті логиканың негіздері
Основы позитивной логики
Keywords: Homomorphisms; positive formulae; inductive limits; inductive classes; universal sentences; compactness; companion theories; model-complete theories